Agmatine rescues autistic behaviors in the valproic acid-induced animal model of autism. (February 2017) - Kim, Ji-Woon; Seung, Hana; Kim, Ki Chan; Gonzales, Edson Luck T.; Oh, Hyun Ah; Yang, Sung Min; Ko, Mee Jung; Han, Seol-Heui; Banerjee, Sourav; Shin, Chan Young
Abstract: Autism spectrum disorder (ASD) is an immensely challenging developmental disorder characterized primarily by two core behavioral symptoms of social communication deficits and restricted/repetitive behaviors. Investigating the etiological process and identifying an appropriate therapeutic target remain as formidable challenges to overcome ASD due to numerous risk factors and complex symptoms associated with the disorder. Among the various mechanisms that contribute to ASD, the maintenance of excitation and inhibition balance emerged as a key factor to regulate proper functioning of neuronal circuitry. Interestingly, our previous study involving the valproic acid animal model of autism (VPA animal model) has demonstrated excitatory-inhibitory imbalance (E/I imbalance) due to enhanced differentiation of glutamatergic neurons and reduced GABAergic neurons. Here, we investigated the potential of agmatine, an endogenous NMDA receptor antagonist, as a novel therapeutic candidate in ameliorating ASD symptoms by modulating E/I imbalance using the VPA animal model. We observed that a single treatment of agmatine rescued the impaired social behaviors as well as hyperactive and repetitive behaviors in the VPA animal model. We also observed that agmatine treatment rescued the overly activated ERK1/2 signaling in the prefrontal cortex and hippocampus of VPA animal models, possibly, by modulating over-excitability due to enhanced excitatory neural circuit. Taken together, our results have provided experimental evidence suggesting a possible therapeutic role of agmatine in ameliorating ASD-like symptoms in the VPA animal model of ASD. Highlights: Single treatment of agmatine rescues social impairment in the VPA-induced animal model of autism. Effect of agmatine in social improvement in the VPA model is induced from agmatine itself, not its metabolite. Agmatine rescues repetitive and hyperactive behavior, and seizure susceptibility in the VPA model. Overly activated ERK1/2 in the brain of the VPA model is relieved by agmatine.